Method for restoring ionic conductivity of ceramic material and method for manufacturing electric storage device
The method of heat treating ceramic materials with flowing inert and oxygen gases in a controlled atmosphere restores their ionic conductivity at lower temperatures, addressing the conductivity loss due to atmospheric exposure and improving power storage device performance.
Patent Information
- Application Number
- JP2021066916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-12
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-04-12
AI Technical Summary
Ceramic materials with lithium ion conductivity experience a decrease in ionic conductivity when exposed to the atmosphere, primarily due to the reaction with CO2, which forms a membrane that reduces conductivity.
A method involving heat treatment in a furnace where inert gas and oxygen gas flow around the ceramic material, reducing the temperature range required for restoring ionic conductivity by removing CO2 and maintaining a lower partial pressure.
This method effectively restores the ionic conductivity of ceramic materials at a lower temperature, enhancing the power density of power storage devices by reducing the internal resistance and grain growth during heat treatment.
Smart Images

Figure 0007659430000001 
Figure 0007659430000002 
Figure 0007659430000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for restoring the ionic conductivity of a ceramic material having lithium ion conductivity, and a method for producing an electricity storage device. [Background technology]
[0002] As a ceramic material having lithium ion conductivity, a synthetic powder or a sintered body having a garnet-type crystal structure containing Li, La, Zr, and O is known. If this ceramic material is left in the air, the ionic conductivity decreases compared to immediately after the synthesis of the synthetic powder or immediately after the sintering of the sintered body. In the technology described in Patent Document 1, a ceramic material with reduced ionic conductivity is heat-treated in a temperature range of 650°C or higher in at least one atmosphere selected from an inert gas atmosphere, an oxygen atmosphere, and a reduced pressure atmosphere, thereby recovering the ionic conductivity. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6018947 Summary of the Invention [Problem to be solved by the invention]
[0004] The reason why the ionic conductivity of ceramic materials decreases is that the ceramic materials are exposed to atmospheric CO 2 reacts with Li on the surface of the ceramic material. 2 CO 3 In the prior art, the CO generated from the ceramic material by heat treatment was 2 The Li of the film is retained around the ceramic material. 2 CO 3 and atmosphere CO 2 To prevent chemical equilibrium between 2 It is necessary to carry out the heat treatment in a temperature range where the partial pressure is sufficiently high.
[0005] The present invention has been made to solve this problem, and aims to provide a method for recovering the ionic conductivity of a ceramic material that can lower the temperature range of heat treatment, and a method for manufacturing an electricity storage device. [Means for solving the problem]
[0006] In order to achieve this object, the present invention provides a method for recovering the ionic conductivity of a ceramic material having lithium ion conductivity, the ceramic material being a synthetic powder or a sintered body having a garnet-type crystal structure composed of at least Li, La, Zr, and O, the ceramic material having a reduced ionic conductivity compared to the ionic conductivity immediately after synthesis of the synthetic powder or immediately after sintering of the sintered body being heat-treated in a furnace into which at least one gas selected from an inert gas and an oxygen gas flows and into which gas flows out, in an atmosphere in which the gas flows around the ceramic material, thereby recovering the ionic conductivity of the ceramic material.
[0007] A method for manufacturing an electricity storage device of the present invention includes a step of disposing a ceramic material with restored ionic conductivity. Effect of the Invention
[0008] CO desorbed from ceramic materials by heat treatment 2 is removed from around the ceramic material by the gas flowing around the ceramic material. 2 Since the partial pressure can be reduced, the ionic conductivity of the ceramic material can be restored even in a low temperature range of the heat treatment. Since the ceramic material with restored ionic conductivity is disposed in the power storage device, the power density of the power storage device can be increased. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a cross-sectional view of the heat treatment apparatus. [Diagram 2] FIG. 1 shows the relationship between temperature and equilibrium CO2 concentration. [Diagram 3] FIG. 2 is a cross-sectional view of the electricity storage device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A preferred embodiment of the present invention will be described below with reference to the accompanying drawings. FIG. 1 is a cross-sectional view of a heat treatment device 10. The heat treatment device 10 includes a furnace 11 and a heating element 12 disposed outside the furnace 11. In this embodiment, the furnace 11 of the heat treatment device 10 is a tubular furnace, but is not limited to this. The heat treatment device 10 may be a furnace 11 of any shape, such as a box furnace. Gas flows into a treatment chamber 13 inside the furnace 11 from an air inlet 14, and the gas in the treatment chamber 13 flows out from an exhaust port 15. A ceramic material 18 placed on a refractory vessel 17 is heat-treated in the furnace 11. The shape of the vessel 17 may be selected as appropriate. A thermocouple 16 detects the temperature in the treatment chamber 13 near the ceramic material 18.
[0011] The ceramic material 18 is an oxide having a garnet-type crystal structure containing Li, La, and Zr. This oxide has lithium ion conductivity. The basic composition of the oxide having a garnet-type crystal structure is Li 5 La 3 M 2 O 12 (M=Nb, Ta). The ceramic material 18 has the basic composition Li 5 La 3 M 2 O 12 Li in which the pentavalent M cation is replaced by a tetravalent cation 7 La 3 Zr 2 O 12 Examples are given below.
[0012] The ceramic material 18 can contain at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, V, Ga, Sr, Y, Nb, Sn, Sb, Ba, Hf, Ta, W, Bi, Rb, and lanthanides (excluding La), in addition to Li, La, and Zr. For example, Li 6 La 3 Zr 1.5 W 0.5 O 12, Li 6.15 La 3 Zr 1.75 Ta 0.25 Al 0.2 O 12 , Li 6.15 La 3 Zr 1.75 Ta 0.25 Ga 0.2 O 12 , Li 6.25 La 3 Zr 2 Ga 0.25 O 12 , Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 , Li 6.5 La 3 Zr 1.75 Te 0.25 O 12 , Li 6.75 La 3 Zr 1.75 Nb 0.25 O 12 , Li 6.9 La 3 Zr 1.675 Ta 0.289 Bi 0.036 O 12 , Li 6.46 Ga 0.23 La 3 Zr 1.85 Y 0.15 O 12 , Li 6.8 La 2.95 Ca 0.05 Zr 1.75 Nb 0.25 O 12 , Li 7.05 La 3.00 Zr 1.95 Gd 0.05 O 12 , Li 6.20 Ba 0.30 La 2.95 Rb 0.05 Zr 2 O 12 include the following.
[0013] Ceramic material 18 preferably contains at least one of Mg and element A (A is at least one element selected from the group consisting of Ca, Sr, and Ba) with the molar ratios of each element satisfying all of the following (1) to (3), or contains both Mg and element A with the molar ratios of each element satisfying all of the following (4) to (6). Element A is preferably Sr in order to increase the ionic conductivity of ceramic material 18. (1) 1.33≦Li / (La+A)≦3 (2) 0≦Mg / (La+A)≦0.5 (3) 0≦A / (La+A)≦0.67 (4) 2.0≦Li / (La+A)≦2.5 (5) 0.01≦Mg / (La+A)≦0.14 (6) 0.04≦A / (La+A)≦0.17.
[0014] The ceramic material 18 may be a synthetic powder or a sintered body (bulk). The shape of the sintered body is not particularly limited, and any shape such as a pellet, a plate, or a film can be appropriately selected. The method for producing the ceramic material 18 includes a blending step of blending raw materials to obtain a blended material, and a firing step of firing the blended material.
[0015] In the blending step, materials containing the elements that constitute the ceramic material 18 are blended to obtain a blended material. Examples of the materials include oxides, composite oxides, hydroxides, carbonates, chlorides, sulfates, nitrates, and phosphates that contain the elements Li, La, Zr, Mg, and A. The materials are pulverized and mixed to obtain the blended material.
[0016] It is preferable to include a calcination step between the blending step and the firing step, in which the blended material is calcined at 900-1100°C for 2-15 hours to obtain a calcined material. By passing through the calcination step, it becomes easier to obtain a garnet-type crystal structure after the firing step.
[0017] It is preferable to include a step of pulverizing and mixing the calcined material between the calcination step and the firing step. In this step, the calcined material is pulverized and mixed to obtain a mixed material. By passing through the step of pulverizing and mixing the calcined material, a uniform crystal phase is easily obtained after the firing step. The calcined material to which a binder has been added may be pulverized and mixed. Examples of the binder include methyl cellulose, ethyl cellulose, polyvinyl alcohol, and polyvinyl butyral.
[0018] In the sintering process, the compounded, calcined or mixed materials are molded, and then the molded body is sintered at, for example, 1000-1250°C for 3-36 hours to obtain a sintered body. The sintered body is crushed in an inert gas atmosphere to obtain a synthetic powder.
[0019] If the ceramic material 18 is left in the air after the synthesis of the synthetic powder or after the sintering of the sintered body, the ceramic material 18 will react with the CO 2 reacts with Li to form on the surface of the ceramic material 18. 2 CO 3 This film reduces the ionic conductivity of the ceramic material 18. In order to restore the ionic conductivity of the ceramic material 18, the ceramic material 18, whose ionic conductivity has decreased compared to the ionic conductivity immediately after the synthesis of the synthetic powder or immediately after the sintering of the sintered body, is heated in a furnace 11 of a heat treatment device 10 through which gas flows in and out.
[0020] The gas flowing into the processing chamber 13 of the furnace 11 from the air inlet 14 of the heat treatment device 10 is at least one selected from an inert gas and oxygen gas. The inert gas is not particularly limited as long as it is a gas that does not chemically react with the ceramic material 18. Examples of the inert gas include nitrogen, helium, neon, argon, krypton, xenon, and radon. In particular, at least one selected from nitrogen, helium, and argon is preferable.
[0021] In the heat treatment device 10, gas is introduced into the treatment chamber 13 from the air inlet 14, and the gas in the treatment chamber 13 is pushed toward the exhaust port 15 by the gas, and is exhausted to the outside of the treatment chamber 13. This allows the treatment chamber 13 to have an atmosphere in which gas flows around the ceramic material 18. The inflow of gas from the air inlet 14 into the treatment chamber 13 and the exhaust of gas from the exhaust port 15 may be continuous or intermittent. In addition, a vacuum pump (not shown) may be connected to the exhaust port 15, the air inlet 14 may be closed, the gas in the treatment chamber 13 may be sucked and exhausted, and then the air inlet 14 may be opened and the gas may be introduced into the treatment chamber 13 from the air inlet 14. This allows the treatment chamber 13 to have an atmosphere in which gas flows intermittently around the ceramic material 18. The flow rate of the gas that flows continuously or intermittently into the treatment chamber 13 and the period of the gas that is intermittently introduced are appropriately set according to the volume of the treatment chamber 13 and the mass of the ceramic material 18 to be heated.
[0022] The gas CO introduced into the treatment chamber 13 from the gas inlet 14 2 The concentration depends on the temperature of the processing chamber 13, but it is 2 The dew point of the gas introduced into the treatment chamber 13 from the gas inlet 14 is preferably -40°C or lower, and more preferably -50°C or lower. 2 This is to promote the release of the ions.
[0023] Figure 2 shows Li 2 CO 3 / L 2 CO at atmospheric pressure in equilibrium with O 2 This is a diagram showing the relationship between concentration and temperature. Figure 2 was created using the following procedure. First, the concentration of Li at each temperature listed in the National Institute of Standards and Technology (NIST) database (https: / / webbook.nist.gov / chemistry / ) was calculated. 2 CO 3 ,Li 2 O and CO 2 The Gibbs energy at each temperature is calculated from the enthalpy and entropy of Li and the equilibrium constant at each temperature is calculated. 2 CO 3=Li 2 O+CO 2 CO at atmospheric pressure and at each temperature in the equilibrium state of the reaction represented by the formula 2 The partial pressure is calculated and plotted to obtain Figure 2.
[0024] According to Figure 2, at 600°C, Li 2 CO 3 / L 2 CO in equilibrium with O 2 The concentration is 5.4 ppm (volume). 2 By adjusting the concentration and flow rate of the gas, the CO 2 The concentration can be reduced to 5 ppm or less. Therefore, the temperature of the treatment chamber 13 during the heat treatment of the ceramic material 18 is preferably 600°C or higher. The heat treatment of the ceramic material 18 can be performed in a temperature range lower than the maximum temperature achieved during the synthesis of the synthetic powder or the sintering of the sintered body. The upper limit temperature for the heat treatment of the ceramic material 18 is, for example, 1250°C.
[0025] The heat treatment time of the ceramic material 18 can be any time that allows the ion conductivity to recover to a desired level. The heat treatment time is appropriately set according to the level of decrease in ion conductivity and the temperature range of the heat treatment. For example, when the heat treatment is performed at a temperature range of 640°C or higher, the heat treatment can be held for 10 hours or more, and when the heat treatment is performed at a temperature range of 670°C or higher, the heat treatment can be held for 2 hours or more.
[0026] CO desorbed from ceramic material 18 by heat treatment 2 is removed from around the ceramic material 18 by the gases introduced into the furnace 11. This removes the atmospheric CO 2Since the partial pressure can be lowered, the ionic conductivity of the ceramic material 18 can be restored even if the temperature range of the heat treatment is low. Since the temperature range of the heat treatment can be lowered, the formation of necks due to bonding between ceramic material 18 (synthetic powder) and the expansion of necks due to diffusion of atoms, etc. during heat treatment can be reduced, and the grain growth of the synthetic powder can be reduced. As a result, the layer containing the synthetic powder in the electricity storage device 20 (described later) can be made thinner, so the transport distance of ions within the layer is shortened and the internal resistance of the layer can be reduced. In addition, since the grain growth of the ceramic material 18 (sintered body) during heat treatment can be reduced, the structure of the sintered body can be controlled.
[0027] Further preferably, following the heat treatment, the ceramic material 18 is cooled in the furnace 11 under an atmosphere of inflow and outflow of at least one gas selected from an inert gas and an oxygen gas. 2 The ceramic material 18 is cooled in this atmosphere until the temperature of the ceramic material 18 becomes, for example, 50° C. or lower.
[0028] The ceramic material 18 (sintered body) after the heat treatment is immediately placed in an electricity storage device 20 (described later). The ceramic material 18 (synthetic powder) after the heat treatment is immediately mixed with a polymer and formed into a sheet, which is then placed in the electricity storage device 20. The electricity storage device 20 is sealed in a container (not shown) that includes a barrier layer made of a metal foil such as aluminum or a vapor deposition layer. In either case, the ceramic material 18 is exposed to CO 2 This is to prevent the particles from being adsorbed.
[0029] 3 is a cross-sectional view of the electricity storage device 20. The electricity storage device 20 in this embodiment is a lithium ion solid state battery in which the power generating element is made of a solid. The power generating element being made of a solid means that the skeleton of the power generating element is made of a solid, and does not exclude, for example, a form in which the skeleton is impregnated with a liquid.
[0030] The electricity storage device 20 includes, in order, a positive electrode layer 21, an electrolyte layer 24, and a negative electrode layer 25. The positive electrode layer 21, the electrolyte layer 24, and the negative electrode layer 25 are housed in a container (not shown).
[0031] The positive electrode layer 21 is formed by stacking a current collecting layer 22 and a composite layer 23. The current collecting layer 22 is a member having electrical conductivity. Examples of the material of the current collecting layer 22 include a metal selected from Ni, Ti, Fe, and Al, an alloy containing two or more of these elements, stainless steel, and a carbon material.
[0032] The composite layer 23 includes a ceramic material 18, an active material 28, and a binder. A conductive additive may be included in the composite layer 23 to reduce the resistance of the composite layer 23. Examples of the conductive additive include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag.
[0033] The active material 28 is exemplified by a metal oxide having a transition metal, a sulfur-based active material, and an organic active material. The metal oxide having a transition metal is exemplified by a metal oxide containing Li and one or more elements selected from Mn, Co, Ni, Fe, Cr, and V. The metal oxide having a transition metal is exemplified by LiCoO 2 ,LiMn 2 O 4 ,LiNiVO 4 ,LiMn 1.5 Ni 0.5 O 4 and LiFePO 4 Examples are given below.
[0034] Sulfur-based active materials include S and TiS 2 ,NiS,FeS 2 ,Li 2 S,MoS 3 Examples of the organic active material include radical compounds such as 2,2,6,6-tetramethylpiperidinoxyl-4-yl methacrylate and polytetramethylpiperidinoxyl vinyl ether, quinone compounds, radialene compounds, tetracyaquinodimethane, and phenazine oxide.
[0035] The binder contained in the composite layer 23 binds the ceramic material 18 and the active material 28. Examples of the binder include polyimide-based, acrylic-based, polysiloxane, polyalkylene glycol, polyvinylidene fluoride, polytetrafluoroethylene, styrene butadiene rubber, ethylene-vinyl alcohol copolymer, and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0036] The electrolyte layer 24 includes the ceramic material 18. When the ceramic material 18 is a synthetic powder, the electrolyte layer 24 includes the ceramic material 18 and a binder. The binder included in the electrolyte layer 24 is similar to that included in the composite layer 23, and therefore a description thereof will be omitted.
[0037] The negative electrode layer 25 is formed by stacking a current collecting layer 26 and a composite layer 27. The current collecting layer 26 is a member having electrical conductivity. Examples of the material of the current collecting layer 26 include a metal selected from Ni, Ti, Fe, Cu, and Si, an alloy containing two or more of these elements, stainless steel, and a carbon material.
[0038] The composite layer 27 includes a ceramic material 18, an active material 29, and a binder. A conductive additive may be included in the composite layer 27 to reduce the resistance of the composite layer 27. Examples of the conductive additive include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag.
[0039] The active material 29 is Li, Li-Al alloy, Li 4 Ti 5 O 12 Examples of the binder include graphite, In, Si, a Si-Li alloy, and SiO. The binder contained in the composite layer 27 is similar to that contained in the composite layer 23, and therefore a description thereof will be omitted.
[0040] The power storage device 20 can achieve high power density because the ceramic material 18 with restored ionic conductivity is disposed therein. EXAMPLES
[0041] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0042] (Preparation of ceramic materials) Li 6.95 Mg 0.15 La 2.75 Sr 0.25 Zr 2.0 O 12 So that Li 2 CO 3 ,MgO,La(OH) 3 ,SrCO 3 ,ZrO 2 Li was weighed. 2 CO 3 Considering the volatilization of Li during firing, the amount was set to about 15 mol% excess in elemental terms. The weighed raw materials and organic solvent were placed in a nylon pot together with zirconia balls, and were ground and mixed in a ball mill for 15 hours. The slurry removed from the pot was dried, and then pre-fired (1100°C for 10 hours) on an MgO plate. The pre-fired powder, binder, and organic solvent were placed in the pot, and were ground and mixed in a ball mill for 15 hours.
[0043] The slurry taken out of the pot was dried, then poured into a die with a diameter of 12 mm and pressed to obtain a green body with a thickness of about 1.5 mm. 2 The compact was covered with calcined powder having the same composition as the compact, and sintered in a reducing atmosphere (at 1100°C for 4 hours) to obtain a sintered compact.
[0044] The lithium ion conductivity of the sintered body immediately after sintering is 1.0×10 -3 S / cm. The ionic conductivity was measured by an AC impedance method. The ionic conductivity was measured under the conditions of a temperature of 25°C, a voltage of 10 mV, and a frequency of 7 MHz-100 mHz. Immediately after sintering, the sintered body was pulverized in a glove box in an Ar atmosphere to obtain a synthetic powder of the ceramic material.
[0045] (Test 1) The resulting synthetic powder was then cooled to room temperature.2 The powder was stored in an Ar atmosphere glove box in the presence of , for 24 hours to obtain a synthesized powder before heat treatment (hereinafter referred to as "powder A").
[0046] The processing chamber 13 of the heat treatment device 10 (volume 1875 cm 3 ) was used to accommodate powder A (40 g or less) placed on vessel 17, and while nitrogen gas was being introduced into treatment chamber 13 from air inlet 14 (flow rate 10 L / min), the gas in treatment chamber 13 was exhausted from exhaust outlet 15. While nitrogen gas was being circulated through treatment chamber 13, furnace 11 was heated by heating element 12 to increase the temperature of treatment chamber 13, and after the temperature of treatment chamber 13 reached 640°C, this state was maintained for 10 hours, and then the temperature was decreased. After the temperature of treatment chamber 13 reached 50°C, the heat-treated synthetic powder (hereinafter referred to as "powder 1") placed on vessel 17 was immediately taken out of furnace 11 and placed in a sealed container to prevent exposure to the atmosphere.
[0047] The ionic liquid 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI-FSI) was mixed with the electrolyte salt LiN(SO 2 F) 2 to 0.8 mol / dm 3 The composite electrolyte and powder 1 were mixed in a mortar so that the volume ratio of powder 1:electrolyte was 80:20 to obtain a composite powder. 0.15 g of the composite powder was placed in a 10 mm diameter cylinder made of an insulator in an Ar atmosphere, and uniaxial compaction was performed by applying a pressure of 500 MPa to obtain a disk-shaped compact. Stainless steel current collectors were attached to both sides of the compact using the axial force of a screw with a tightening torque of 8 N, and the total ionic conductivity of the compact containing powder 1 was measured under the same conditions as for measuring the ionic conductivity of the sintered compact. The electrolyte was combined with the powder in order to reduce the effect of grain boundary resistance of the powder.
[0048] In the same manner, a composite powder of Powder A and the electrolyte was prepared, a compact was made, and the total ionic conductivity of the compact containing Powder A was measured. The total ionic conductivity of the compact containing Powder 1 was 1.6 times that of the compact containing Powder A. It was revealed that the ionic conductivity of the ceramic material was restored by heat treatment at 640°C for 10 hours.
[0049] (Test 2) The furnace 11 was heated, and after the temperature of the processing chamber 13 reached 670°C, that state was maintained for two hours, and then the temperature was lowered. The heat treatment conditions were the same as those for powder 1, and a synthetic powder after heat treatment (hereinafter referred to as "powder 2") was obtained.
[0050] A vacuum pump (not shown) was connected to exhaust port 15, air inlet port 14 was closed, and the gas in processing chamber 13 was sucked out and then exhaust port 15 was closed and air inlet port 14 was opened to introduce nitrogen gas into processing chamber 13 through air inlet port 14. The furnace 11 was heated with air inlet port 14 and exhaust port 15 closed (under a sealed nitrogen gas atmosphere), and after the temperature of processing chamber 13 reached 700°C, this state was maintained for 2 hours before the temperature was lowered, and a heat-treated synthetic powder (hereinafter referred to as "Powder B") was obtained under the same heat treatment conditions as those for Powder 1.
[0051] The furnace 11 was heated under a nitrogen gas atmosphere with the air inlet 14 and the exhaust outlet 15 closed, and after the temperature of the processing chamber 13 reached 800°C, this state was maintained for two hours and then the temperature was lowered. The same heat treatment conditions were used as for Powder B, except that the temperature was then lowered, to obtain a heat-treated synthetic powder (hereinafter referred to as "Powder C").
[0052] In the same manner as in Test 1, Powder 2, Powder B, and Powder C were each compounded with an electrolyte solution, and compacts containing Powder 2, Powder B, and Powder C were prepared, respectively, and the total ionic conductivity of the compacts was measured. The total ionic conductivity of the compact containing Powder 2 was 1.4×10 -3 S / cm, and the total ionic conductivity of the compact containing powder B is 1.1×10 -3 S / cm, and the total ionic conductivity of the compact containing powder C is 1.3×10 -3 It was S / cm.
[0053] It was revealed that Powder 2 could have a high ion conductivity even though it was heat-treated at a lower temperature than the heat-treatment temperatures of Powder A and Powder B. This example revealed that when restoring a ceramic material to an equivalent lithium ion conductivity, the temperature range of the heat treatment can be made lower than when the heat treatment is performed in a sealed inert gas atmosphere.
[0054] The present invention has been described above based on an embodiment, but the present invention is in no way limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.
[0055] In the embodiment, the electricity storage device 20 has been described as including the positive electrode layer 21 in which the composite layer 23 is provided on one side of the current collecting layer 22, and the negative electrode layer 25 in which the composite layer 27 is provided on one side of the current collecting layer 26, but the present invention is not necessarily limited to this. For example, it is naturally possible to place the ceramic material 18 in the embodiment in an electricity storage device including an electrode layer (so-called bipolar electrode) in which the composite layer 23 and the composite layer 27 are provided on both sides of the current collecting layer 22. If the bipolar electrodes and the electrolyte layer 24 are alternately stacked and housed in a container (not shown), a so-called bipolar structure electricity storage device can be obtained.
[0056] In the embodiment, the electricity storage device 20 in which the positive electrode layer 21 and the electrolyte layer 24 are adjacent to each other and the negative electrode layer 25 and the electrolyte layer 24 are adjacent to each other has been described, but the present invention is not necessarily limited to this. It is of course possible to dispose an intermediate layer containing the ceramic material 18 between the positive electrode layer 21 and the electrolyte layer 24 or between the negative electrode layer 25 and the electrolyte layer 24.
[0057] In the embodiment, the case where the composite layers 23, 27 and the electrolyte layer 24 all contain the ceramic material 18 has been described, but this is not necessarily limited to this. It is sufficient that the electricity storage device 20 contains the ceramic material 18 in at least one of the composite layers 23, 27 and the electrolyte layer 24.
[0058] In the embodiment, the electricity storage device 20 including the electrode layers (positive electrode layer 21 and negative electrode layer 25) and the electrolyte layer 24 has been described using a lithium ion solid-state battery (secondary battery) as an example, but is not necessarily limited to this. Other electricity storage devices include batteries using sulfur in the positive electrode (for example, LiS batteries in combination with lithium in the negative electrode), lithium-air batteries, and electrolytic capacitors. [Explanation of symbols]
[0059] 11 Furnace 18 Ceramic Materials 20 Energy storage devices
Claims
1. 1. A method for restoring ionic conductivity to a ceramic material having lithium ion conductivity, comprising: The ceramic material is a synthetic powder or a sintered body having a garnet-type crystal structure composed of at least Li, La, Zr, and O; The method includes subjecting the ceramic material, the ionic conductivity of which has decreased compared to the ionic conductivity immediately after the synthesis of the synthetic powder or immediately after the sintering of the sintered body, to a heat treatment in a furnace into which at least one gas selected from an inert gas and an oxygen gas flows and from which the gas flows out, in an atmosphere in which the gas flows around the ceramic material, thereby recovering the ionic conductivity of the ceramic material.
2. The method of claim 1 , wherein the heat treatment comprises maintaining the temperature in a range of 640° C. or more for 10 hours or more.
3. The method of claim 1 , wherein the heat treatment comprises maintaining the temperature in a range of 670° C. or more for 2 hours or more.
4. 4. The method according to claim 1, further comprising the step of cooling the ceramic material in the furnace under an inflow and outflow atmosphere of at least one gas selected from an inert gas and an oxygen gas following the heat treatment.
5. The method according to any one of claims 1 to 4, wherein the gas is an inert gas.
6. A method for manufacturing an electricity storage device including one or more of an electrode layer, an electrolyte layer, and an intermediate layer arranged between the electrode layer and the electrolyte layer, comprising a step of placing a ceramic material whose ionic conductivity has been restored by a method described in any one of claims 1 to 5 in one or more of the electrode layer, the electrolyte layer, and the intermediate layer.
Citation Information
Patent Citations
Metal-oxide-semiconductor chip of disk memory control circuit
JP1985018947A
Method for restoring ion conductivity of solid electrolyte ceramic material
JP2013219017A